Ukrainian baroque in visual arts – national symbols in the context of european culture - S. P. Stoian, (Ukrainian Cultural Studies, 2021)
The article studies the peculiarities of visual image symbolic type originating in the artistic practice of Ukrainian baroque. It is stated that baroque culture of 17-18 cent. was spreading across Ukrainian territories. Meanwhile Ukrainian art of that period was developing in close interaction with the art of Central Europe, Russia and Balkan countries. Realistic traditions of Western Europe were actively taking roots on Ukrainian territory thus forming the alternative for sacral orthodox art.  Symbolic and allegoric type of visual art is mostly used for didactic and educational aims  (I. Galyatovsky), narrative ones (I. Bondarevska) and to be more precise and clear it is accompanied by text explanations. Symbolic motives are also represented in virtually all works of H. Skovoroda distinguishing purely symbolic images and fantastic ones. He believes that symbolic imagery is a "picture of wisdom". Emblem-embedded and symbol-embedded books with symbolic and allegoric illustrating engravings become more common and widespread due to the typography development. Publication of "Symbola et Emblemata" and "Iphika Hieropolitica" promotes the usage of these murals, icon paintings, and didactic motives of secular arts. Symbolic and allegoric contents of ethno-national coloring fill the imagery of Ukrainian national icon paintings ("Cossack Mamay", etc.) and symbolically-allegoric compositions of icon paintings ("Jesus Christ the Husbandman", "The Eye of Providence", "Crucifixion with Vine", "Christ in the Winepress", etc.). Also allegoric motives are used in parsuna genre.The article states that, due to the rationalistic tendency influence of European culture, Ukrainian visual art of baroque period moves away from Byzantine canons with their symbolic conventionality thus turning more and more to realistic type of imagery (especially in portrait genre) and at the same time retaining symbolic and allegoric techniques which gained some ethno-national peculiarities.
Keywords: Ukrainian baroque, symbolism, symbol, allegory, visual art, culture